UJI SITOTOKSISITAS DAN AKTIVITAS ANTIANGIOGENESIS EKSTRAK ETANOLIK ANGGREK MERPATI (Dendrobium crumenatum Swartz.) - , ATIEK KUSMIYATI, Dr. biol. hom. Nastiti Wijayanti, S.Si., M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Genera Dendrobium has been used and known for long time as medicine for treatment and preventing of several diseases such as antihyperglicemic, antioxidant, antiinflamation and anticancer. Dendrobium is reported having anticancer activities both in vivo and in vitro. Dendrobium crumenatum Swartz. commonly known as pigeon orchid or sparrow orchid (Anggrek Merpati) is one kind of special orchids in the tropical country because it has very unique flower characteristic such as whitish fragrant flower that looks like a pigeon. In an empirical manner, this orchid is popular as traditional medicine material, this orchid also guess having potency as anticancer, however, its potency is not completely study yet. The main purposes of this research are to determine the cytotoxicity effect of ethanolic extracts from Dendrobium crumenatum Swartz. leaves and pseudobulbs on cervix cancer (HeLa) cell lines in vitro and to determine antiangiogenesis activity with chorio allantoic membrane (CAM) method in embryonated eggs as an in vivo model. Experiment was initiated by extracting the leaves and pseudobulbs using 96% ethanol by maceration. The activity of Dendrobium crumenatum Swartz. leaves and pseudobulbs ethanolic extracts to inhibit the growth of HeLa cancer cell lines was determine by MTT assay. IC50 value was determined by probit analysis based on MTT assay. IC50 values for ethanolic extracts from leaves and pseudobulbs were 153.828 and 166.180 Î¼g/ml. Antiangiogenesis activity with chorio allantoic membrane (CAM) method in embryonated eggs was done based on the smallest IC50 value, which is using leaves ethanolic extract. In this research angiogenesis was induced by bFGF as a positive control. At concentration 76.914 Î¼g/ml succeeded in giving greatest inhibition, inhibition percentage was 64.77%. This results indicated a potential anticancer candidate of Dendrobium crumenatum Swartz. leaves ethanolic extract